Herbal Rujak Soup Accelerates Uterine Involution On Postpartum Mothers - Mariati Mariati; Afrina Mizawati; Ferly Yorenza (STIKes Patria Husada Blitar, 2023)
According to the World Health Organization (WHO) in 2021, the highest mothers’ mortality rate cases occurred in Africa with 525 deaths per 100,000 live births and the lowest was in Europe with 13 deaths per 100,000 live births. The most common cause of mothers mortality rate in Indonesia in 2019 was caused by several cases such as bleeding (30.32%). Uterine atony occurs due to failure of uterine contractions to control bleeding after delivery, causing uterine subinvolution. This process is known as uterine involution. The herbal composition of rujak soup is useful for preventing blood clots due to a compound called gingerol in ginger. The type of research used in this study was a quasi-experiment with a two-group post-test design. The population in this study was postpartum mothers from the first day to the tenth day of postpartum at PMB F Bengkulu City as many as 117 people with a sample of 30 respondents. The statistical test used was the Independent T-test. The results of this study indicate that the average acceleration of uterine involution on the seventh day is known that in the herbal soup rujak group is 4.73 and the uterine involution acceleration in the palm juice group is 5.40 with a mean difference between the herbal kuah rujak group and the date palm juice group. 0.67. There was an effect between the group of herbal ingredients of rujak sauce and the palm juice group on the TFU on day 7 with a p value = 0.038 and a mean difference of 0.67. This proves that the herbal rujak soup accelerates uterine involution more. It is hoped that the PMB of the Telaga Dewa Working Area will continue to promote complementary medicine with herbal ingredients to reduce the use of chemical drugs and help deal with problems during the postpartum period